2021
DOI: 10.4012/dmj.2021-052
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effects and physical properties of a glass ionomer cement containing BioUnion filler with acidity-induced ability to release zinc ion

Abstract: BioUnion filler is a bioactive glass particle that releases Zn 2+ in an acidic environment. In this study, the ion release, antibacterial, and physical properties of a glass ionomer cement (GIC) incorporating BioUnion filler (CA) were assessed in vitro. The concentration of Zn 2+ released from CA into acetic acid was higher than that released into water and its minimum inhibitory concentrations against six oral bacterial species. Moreover, the concentration of Zn 2+ -release was maintained during all the seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Contrarily, no significant difference in the number of bacterial cells in the biofilm and the volume of the biofilm was found between conventional fluoride-releasing GIC and resin composites. Therefore, the results obtained in this study were comparable to those previously reported by simple in vitro testing demonstrating that BioUnion filler-containing GICs inhibit the growth and adherence of oral bacteria more effectively than conventional fluoride-releasing GICs 41 , 42 . Based on these findings, the in vitro culture system established in the present study is suitable for evaluating the efficacy of restorative materials with antibacterial and anti-biofilm effects.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Contrarily, no significant difference in the number of bacterial cells in the biofilm and the volume of the biofilm was found between conventional fluoride-releasing GIC and resin composites. Therefore, the results obtained in this study were comparable to those previously reported by simple in vitro testing demonstrating that BioUnion filler-containing GICs inhibit the growth and adherence of oral bacteria more effectively than conventional fluoride-releasing GICs 41 , 42 . Based on these findings, the in vitro culture system established in the present study is suitable for evaluating the efficacy of restorative materials with antibacterial and anti-biofilm effects.…”
Section: Discussionsupporting
confidence: 89%
“…The GIC containing BioUnion filler for root surface restoration (Caredyne ® Restore) is currently in the market. The closed-system biofilm model (i.e., incubation under static conditions) was used to demonstrate that acidity-induced release of Zn 2+ from the GIC containing BioUnion filler effectively inhibited the growth and adherence of Streptococcus mutans , S. sobrinus, S. oralis, S. mitis , Actinomyces naeslundii , and Fusobacterium nucleatum 41 . Previously, we developed a saliva-drop setting assembly that can flow AS at 32 mL/h and drop acetate buffer solution (pH 4.5) three times per day to simulate in vivo conditions of the oral cavity, to investigate the ion releasing properties of BioUnion filler-containing and conventional fluoride-releasing GICs 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc is one of these ions known to inhibit oral bacteria. Liu et al reported that the release of Zn 2+ from the BioUnion filler, a glass powder composed of silicon dioxide (SiO 2 ), zinc oxide (ZnO), calcium oxide (CaO), and fluorine (F), accelerated under acidic conditions at a pH of 4.5 [ 15 , 16 , 17 ]. Thus, such technology enables the on-demand release of antimicrobial components from restorative materials.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, such technology enables the on-demand release of antimicrobial components from restorative materials. Liu et al also reported that the acidity-induced release of Zn 2+ from the glass ionomer cement (GIC) containing BioUnion filler (Caredyne ® Restore, GC Corp., Tokyo, Japan) effectively inhibited the growth and adherence of acidogenic bacteria [ 17 ].…”
Section: Introductionmentioning
confidence: 99%